2007
DOI: 10.1037/1555-6824.16.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Supervision can be playful, too: Play therapy techniques that enhance supervision.

Abstract: The use of play therapy techniques within supervision can enhance the supervisory process and in turn therapy with the client. Just as children use toys rather than words to express themselves in play therapy, so too can supervisees use play therapy techniques when words fail to express their experience or understanding of their clients. In this article, the authors focus on L. D. Borders and G. Leddick's (1987) 6 categories for supervisor intervention: learning goals, learning style, experience, developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…This is consistent with previous literature related to play therapy supervision (Mullen et al, 2007;Ray, 2011;Smith-Adcock et al, 2012). In the current study, students reported critical incidents in a play therapy practicum, which in their view, helped to define their development as a counselor.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous literature related to play therapy supervision (Mullen et al, 2007;Ray, 2011;Smith-Adcock et al, 2012). In the current study, students reported critical incidents in a play therapy practicum, which in their view, helped to define their development as a counselor.…”
Section: Discussionsupporting
confidence: 93%
“…Because ST can be utilized within a variety of theoretical approaches, such as Person Centered, Jungian, Adlerian, Gestalt, Developmental, and Psychodynamic (Isom et al, 2015;McCurdy & Owen, 2008;Perryman et al, 2016), supervisors have a range of ways in which they can incorporate ST into extant supervision models (Anekstein et al, 2014;Carnes-Holt et al, 2014;Stark, Frels, & Garza, 2011). For example, Garrett (2015b) described use of journaling as an extension of the ST experience in supervision, while others incorporate photography, painting and drawing, or titling, as well as various forms of narrative and reflective practices (Luke, 2008;Mullen et al, 2007). Although the literature does not suggest an ideal theoretical lens or creative approach, Perryman et al (2016) indicated that the selection of a theoretical lens should be based on several factors, such as one's training, supervisee or supervisor development level, context, population, and supervisory relationship.…”
Section: Sand Tray: a Creative Approachmentioning
confidence: 99%
“…Despite the gap in the literature, creative arts, particularly ST, have been identified as a useful tool or intervention for professional counselors, counselor educators, and supervisors (Gladding, 2010;Mullen, Luke, & Drewes, 2007;Paone et al, 2015;Perryman, Moss, & Anderson, 2016). Fur-ther, ST has been identified as an underutilized framework for developing student or supervisees' multicultural competence (Paone et al, 2015), especially when working with marginalized populations.…”
Section: Introductionmentioning
confidence: 99%
“…The field of social work typically relies on the field practicum model to teach generalist social work practice skills at the bachelor's and master's level, with skill review taking place during a weekly seminar class and feedback provided at the end of the semester through a supervisory evaluation. Historically, teaching play therapy skills, the advanced practice skills taught in this case study course, has included a strong focus on the experiential process, although little research has been conducted on what quantifies effective play therapy instruction, and none of these articles specifically focuses on the setting of the instruction (Lindo et al, 2016, Mullen, Luke, & Drewes, 2007. A limited number of graduate training programs concentrate exclusively on play therapy, but prior research has shown that general hands-on play therapy experience in the classroom can improve students' attitudes, skills, and knowledge about play therapy (Kao & Landreth, 2007;Periera & Smith-Adcock, 2015).…”
Section: Experiential Learning To Teach Generalist Practice and Advanmentioning
confidence: 99%